1970
DOI: 10.3329/jdmc.v18i2.6275
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hepatitis-B Among Healthcare Professionals due to Medical Waste Handling

Abstract: The incidence of hepatitis-B among health care workers due to medical waste handling has been a subject of interest. A hospital base survey was done in Chittagong Medical College Hospital (CMCH), Chittagong during the period of April 2009 through June 2009 among health care workers was done to identify the problem. All types of health care workers especially those are very much vulnerable to needle stick puncture like nurses, ward boys, cleaners, laboratory technicians and doctors were included in this study.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…This was shown by research finding from India which reported a significantly higher incidence of HBsAg occurred among those with history of frequent and occasional needle pricks as compared to those with rare or no needle pricks [13].Also the study finding was comparable with a study conducted in Pakistan Chittagong Medical College Hospital (CMCH), Chittagong, their 66% respondent were victims and all needle stick and sharp injured were positive for HBsAg [14 ]and also in agreement with other report, which was done previously from different regions including Sub-Saharan African countries [15].…”
Section: Discussionsupporting
confidence: 78%
“…This was shown by research finding from India which reported a significantly higher incidence of HBsAg occurred among those with history of frequent and occasional needle pricks as compared to those with rare or no needle pricks [13].Also the study finding was comparable with a study conducted in Pakistan Chittagong Medical College Hospital (CMCH), Chittagong, their 66% respondent were victims and all needle stick and sharp injured were positive for HBsAg [14 ]and also in agreement with other report, which was done previously from different regions including Sub-Saharan African countries [15].…”
Section: Discussionsupporting
confidence: 78%